A new Dryadella Luer (Orchidaceae: Pleurothallidinae) from the South Atlantic Rainforest - Imig, Daniela Cristina; Mancinelli, Werner Siebje; Smidt, Eric De Camargo (Phytotaxa, 2021)
Dryadella catharinensis, a new orchid species found in the north-northeast part of the Santa Catarina state, in southern Brazil, is described here. The tiny new species was found in the dense ombrophilous submontane forest (Floresta Ombrófila Densa Submontana) in the Atlantic Rainforest. It is similar to Dryadella susanae, which is endemic of the Espírito Santo state and differs in the larger vegetative size, the narrow and suberect leaf, yellow flowers, the sepals with slightly denticulate margins, the petals with an obtuse apex and the cuneate lip with denticulated margins and a annular callus in the median portion of the claw. It is the fifteenth Dryadella species restricted to the Atlantic Rainforest (~25% of the genus), evidencing the importance of the conservation of this biome—of which only 11% remains—for the genus. Due to the rarity and low density of this species in the field, allied to the degradation of the habitat, we suggest a conservation status of Endangered. Further fieldwork is needed to locate additional populations and study the biological aspects for their conservation.